The Effect of Profitability and Capital Structure on Firm Value with Dividend Policy as an Intervening Variable - Friska Dwi; Mardiyani (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to examine the effect of profitability and capital structure on firm value with dividend policy as an intervening variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This study employed a quantitative approach with a causal associative design. Secondary data were obtained from the companies' annual financial statements, and the samples were selected using purposive sampling based on predetermined criteria. Data analysis was conducted using path analysis with the assistance of LISREL 8.8 software. The findings indicate that profitability has no significant effect on dividend policy, whereas capital structure has a significant effect on dividend policy. Profitability and capital structure significantly affect firm value, while dividend policy does not significantly affect firm value. In addition, dividend policy is unable to mediate the effect of profitability on firm value, but it is capable of mediating the effect of capital structure on firm value. These findings suggest that firm value in the food and beverage manufacturing subsector is more strongly influenced by the company's ability to generate profits and manage its capital structure optimally than by its dividend policy. Therefore, dividend policy tends to function as a mechanism that transmits the effect of capital structure on firm value rather than as a factor that directly enhances firm value.